Resident's perception and effective spatial planning and design on property crime /cby Nurfadilah Bt Saadul Kurzi - Nurfadilah Saadul Kurzi (Kulliyyah of Architecture and Environmental Design, IIUM, 2011)
Shelter is a basic need of human life that needs to be met on a priority basis. Its definition in a widest sense includes an area of protection which assures/guarantees safe and secure environment. As crime rates keep on increasing especially property crime, the crime-prevention measure aspect has been taken into consideration in designing housing planning all over the world. The adverse effect of the crime in housing and community development has been highlighted in the literature. It is found that, crime cases had encouraged the fear of crime and simultaneously affected the quality of life. The levels of fear are different according to demographic background, for examples, gender and age, yet they are not significantly different according to the crime rates. This research involved three stages. Firstly, the questionnaires were distributed and observations were carried out to identify the background and the planning and design concept of six detailed areas in Petaling Jaya (PJ). Secondly, the results obtained were analysed using the Statistical Package for the Social Sciences (SPSS). In addition, the spatial and street plan analyses were conducted to analyse the concept and pattern of the design as well as to strengthen the statistical analysis. Finally, the relationship between demographic background and the levels of fear of crime was explored using correlation tests. Furthermore, spatial and street mapping were used to identify the planning and design variables that influenced crime activities. The results were utilised for a comparison between three levels of crime, and to see the relationship between related variables. The findings showed that the spatial planning and design affected the crime incidences. The passive design especially on the space organisation and function, street design and landscape ornament and maintenance contribute to provide a safer and comfortable environment. Furthermore, social interaction becomes the most essential part especially to develop an effective surveillance by residents. In a nutshell, this study demonstrated that the effective spatial planning and design must be emphasised in the neighbourhood development in order to provide an alternative to the physical prevention method.